Investigação do modo sul de precipitação no clima presente e futuro no Rio Grande do Sul - Pampuch, Luana Albertani (2010)
This paper presents a mode of variability of precipitation that influence in southern Brazil, called South Mode. We tried to show that the occurrence of events Mode south of precipitation are related to the occurrence of extreme events of rainfall in Rio Grande do Sul, as storm, flood, hail and drought. Using principal component analysis of daily rainfall data filtered in the band 10/50 days, are found spatial and temporal fields that represent the maximum variance of certain variability, and then are detected modes of precipitation variability. Thus it was possible to determine the mode of variability that appears well set in the Rio Grande do Sul and has core between 25 ° S and 35 ° S latitude and 52 ° W and 62 ° W longitude. This mode presents alternating between positive and negative signals, and these may be related to extreme events. The series of principal components was used to select these events. Principal components larger (smaller) than 1.35 (-1.35) times standard deviations are related to events of extreme wet (dry) of precipitation. The South Mode was calculated for the period from 01/03/1982 to 31/05/2006 for the rainfall real data and for the Regional Model RegCM3 data. On decadal analysis it was concluded that the 80 to 90, 90 and 80 for 2000 to 2000 there was a general increase in the occurrence of these events for both the rainfall data, and to model data. The increase found from 1980 to 2000 was more significant. Shown the importance of South mode for precipitation in the Rio Grande do Sul in the current period, the same methodology was used to model data of future climate. The period used was 01/03/2070 to 31/05/2086 for two different emission scenarios: A2 (said pessimistic) and B2 (optimistic). It was concluded that both the dry and rainy events tend to be more extreme in that period for the two emission scenarios. On decadal analysis, we observed a significant increase in the occurrence of rainfall events when compared to the decades of 2000 and 2070 and 2000 and8 2080 in both scenarios. This paper is divided into six chapters dealing respectively with: a literature review, collection and analysis, occurrence of South Mode in rainfall data, occurrence of South Mode in model data, South Mode in future climate data, synoptic analysis of some events of South Mode, and the final considerations of the author.